The role of regulation and regional government quality for high growth firms: The good, the bad, and the ugly - Sara Amoroso; Benedikt Herrmann; Alexander Kritikos (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
High growth firms (HGFs) are important for job creation and considered to be precursors of economic growth. We investigate how product- and labor-market regulations, as well as the quality of regional governments that implement these regulations, affect HGF development across European regions. Using data from Eurostat, OECD, WEF, and Gothenburg University, we show that both regulatory stringency and the quality of the regional government influence the regional shares of HGFs. Additionally, we find that the effect of labor- and product-market regulations ultimately depends on the quality of regional governments. The institutional quality has a moderating role in defining the effect of regulations on the regional shares of HGFs. Our findings contribute to the debate on the effects of regulations by showing that regulations are not, per se, "good, bad, and ugly", rather their impact depends on the efficiency of regional governments. Our paper offers important building blocks to develop tailored policy measures that may influence the development of HGFs in a region.
Keywords: L50; L25; H11; O43; R11; R50; 330; Business dynamics; Regulation; Institutions; Regional data